The Relationship between Sexual Satisfaction and Genital Self-image in Infertile Women - Nahid Marvi; Nahid Golmakani; Habibolah Esmaily; Hossein Shareh (Mashhad University of Medical Sciences, 2018)
Background & aim: In most cases, infertility can have a profound impact on sexual relationship. In such a condition, individuals often have unpleasant feelings towards their bodies, lose their self-confidence, feel depressed and frustrated, and experience decreased sexual desire. Therefore, we sought to investigate the relationship between sexual satisfaction and genital self-image among infertile women. Methods: This cross-sectional study was conducted on 102 infertile women visiting Milad Infertility Center in Mashhad, Iran, during 2016. To select the participants, the convenience sampling method was used. The inclusion criteria were being Iranian and Muslim, having basic literacy, being aged 18-40 years, living with the spouse, not becoming pregnant after about one-year of regular and unprotected sexual intercourse, having a primary diagnosis of infertility as confirmed by a gynecologist, and being formally married. Moreover, the data collection instruments included a demographic form, the Female Genital Self-image Scale, and Golombok-Rust Inventory of Sexual Satisfaction. To analyze the data, Mann-Whitney U test, Chi-square test, Pearson product-moment correlation, and linear regression analysis were run in SPSS, version 16. Results: The mean scores of genital self-image and sexual satisfaction in infertile women were 47.40±9.71 and 61.03±9.81, respectively, indicating a significant correlation between genital self-image and sexual satisfaction in infertile women (r=-0.500, P